Nanostructured and subwavelength waveguides : fundamentals and applications - Skorobogatiy, Maksim, 1974-; Wiley InterScience (Online service) (Hoboken, N.J. ; Chichester : Wiley, 2012)
"Optical waveguides take a prominent role in photonics because they are able to trap and to transport light efficiently between a point of excitation and a point of detection. Moreover, waveguides allow the management of many of the fundamental properties of light and allow highly controlled interaction with other optical systems. For this reason waveguides are ubiquitous in telecommunications, sensing, spectroscopy, light sources, and high power light delivery. Nanostructured and subwavelength waveguides have additional advantages; they are able to confine light at a length scale below the diffraction limit and enhance or suppress light-matter interaction, as well as manage fundamental properties of light such as speed and direction of energy and phase propagation."--
Hamiltonian Formulation of Maxwell Equations for the Modes of Anisotropic Waveguides -- Wave Propagation in Planar Anisotropic Multilayers, Transfer Matrix Formulation -- SlabWaveguides Made from Isotropic Dielectric Materials. Example of Subwavelength Planar Waveguides -- SlabWaveguides Made from Anisotropic Dielectrics -- Metamaterials in the Form of All-Dielectric Planar Multilayers -- Planar Waveguides Containing All-Dielectric Metamaterials, Example of Porous Waveguides -- Circular Fibres Made of Isotropic Materials -- Circular Fibres Made of Anisotropic Materials -- Metamaterials in the Form of a Periodic Lattice of Inclusions -- Circular Fibres Made of All-Dielectric Metamaterials -- Modes at the Interface between Two Materials -- Modes of a Metal Slab Waveguide -- Modes of a Metal Slot Waveguide -- Planar Metal/Dielectric Metamaterials -- Examples of Applications of Metal/Dielectric Metamaterials -- Modes of Metallic Wires, Guidance in the UV-Near-IR, Mid-IR and Far-IR Spectral Ranges -- Semianalytical Methods of Solving Nonlinear Equations of Two Variables.
Includes bibliographical references and index.
Print version record.
Keywords: Optical wave guides; Optoelectronic devices; Nanostructured materials; TECHNOLOGY & ENGINEERING -- Optics; Nanostructured materials; Optical wave guides; Optoelectronic devices; Electronic books